2007
DOI: 10.1007/s10681-007-9587-z
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability for yield and fibre characteristics in Tanzanian cotton germplasm

Abstract: In Tanzania, cotton is of great economical importance, representing a large percentage of agricultural exports, but yield and lint quality is still relatively poor. The aim of this study was to identify parents to improve boll and lint yield and quality. Parents and F1 progeny of a 7 £ 7 diallel were evaluated in four diVerent environments. Results indicated signiWcant variation for especially yield components, yield, ginning outturn and Wbre quality. Parents with high and positive GCA like NTA 93-21, Delcot 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 10 publications
3
13
2
Order By: Relevance
“…Studies of Shakeel et al (2001) and Ahuja and Dhayal (2007) revealed that number of bolls, boll weight and seed cotton yield were influenced by the genes acting non-additively and in contrast studies of Khan and Idris (1995), and Kumaresan et al (1999) indicated that both additive and nonadditive gene effects were important for controlling number of bolls and seed cotton yield. However, Lukange et al (2007) revealed additive gene effects for fibre strength and microanire value and non-addidive gene action for fibre length. Non-additive gene action for fibre quality traits: fibre length, fibre strength and micronaire value have been reported by Baloch et al (1997), Hassan et al (1999 and2000), Ahuja and Dhayal (2007) and Preetha and Raveendran (2008).…”
Section: Discussionmentioning
confidence: 92%
“…Studies of Shakeel et al (2001) and Ahuja and Dhayal (2007) revealed that number of bolls, boll weight and seed cotton yield were influenced by the genes acting non-additively and in contrast studies of Khan and Idris (1995), and Kumaresan et al (1999) indicated that both additive and nonadditive gene effects were important for controlling number of bolls and seed cotton yield. However, Lukange et al (2007) revealed additive gene effects for fibre strength and microanire value and non-addidive gene action for fibre length. Non-additive gene action for fibre quality traits: fibre length, fibre strength and micronaire value have been reported by Baloch et al (1997), Hassan et al (1999 and2000), Ahuja and Dhayal (2007) and Preetha and Raveendran (2008).…”
Section: Discussionmentioning
confidence: 92%
“…These results confirm the findings of Iqbal et al (2005) who reported overdominance type of gene action for seed cotton yield. However, Tang et al (1993), McCarty et al (1996), Ahmad et al (1997), Godoy and Palomo (1999), Hussain et al (1999), Khan (2003), Lukonge (2005), Wu et al (2006), Aguiar et al (2007), Lukonge et al (2007) and Khan et al (2007) reported additive type of genetic control for seed cotton yield. The discrepancies with respect of phenotypic manifestation of this complex parameter might be due to different cultivars used under different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the use of genotypes with desirable genetic components of variance is a prerequisite for synthesis of physiologically efficient and genetically superior genotypes showing promise for increased production per unit area under a given set of environments (Khan et al, 2009a). To achieve these objectives using quantitative genetics, workers have advocated a comprehensive study of assumptions of additive-dominance model (through different scaling tests), genetic mechanism and genetic components of variation which control the various plant characters in parents and their cross combinations under various environmental conditions (Hayman, 1954;Mather and Jinks, 1982;Tang et al, 1993Tang et al, , 1996McCarty et al, 1996McCarty et al, , 2004aHussain et al, 1999;Khan, 2003;Ragsdale, 2003;Lukonge, 2005;Mei et al, 2006;Wu et al, 2006;Esmail, 2007;Lukonge et al, 2007;Khan et al, 2007Khan et al, , 2009aAguado et al, 2008;Ali et al, 2008;Ali and Awan, 2009;Basal et al, 2009;Gamal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Shakeel et al (2001) and Ahuja and Dhayal (2007) revealed that number of bolls, boll weight and seed cotton yield were influenced by the genes acting non-additively and in contrast studies of Khan and Idris (1995), and Kumaresan et al (1999) indicated that both additive and nonadditive gene effects were important for controlling number of bolls and seed cotton yield. However, Lukange et al (2007) revealed additive gene effects for fibre strength and microanire value and non-addidive gene action for fibre length. Non-additive gene action for fibre quality traits: fibre length, fibre strength and micronaire value have been reported by Baloch et al (1997), Hassan et al (1999 and, Ahuja and Dhayal (2007) and Preetha and Raveendran (2008).…”
Section: Discussionmentioning
confidence: 92%